Pulicaria gnaphalodes powder in broiler diets: consequences for performance, gut health, antioxidant enzyme activity, and fatty acid profile. (23rd January 2019) - Shirani, V; Jazi, V; Toghyani, M; Ashayerizadeh, A; Sharifi, F; Barekatain, R
ABSTRACT: The search constantly continues to identify potential alternatives to the use of antimicrobial growth promoters (AGP ) in broiler production. This trial was conducted with broiler chicks to investigate the effect of different levels of Pulicaria gnaphalodes powder (PGP ) in comparison with AGP, and probiotic (PRO) on growth performance, gut microflora, intestinal morphology, antioxidant enzyme activity, and fatty acid profile of meat. Ross 308 male broiler chicks (n = 576) were randomly assigned into 6 dietary treatments with 8 replicate pens per treatment and 12 birds per pen. The dietary treatments consisted of a basal diet as control (CON, with no additive), CON + 0.1% PGP, CON + 0.2% PGP, CON + 0.3% PGP, CON + 0.1% probiotic mixture (PRO), and CON + 0.05% bacitracin methylene disalicylate (AGP). Higher body weight gain and lower feed conversion ratio were obtained in birds fed AGP and 0.3% PGP compared with those fed CON and 0.1% PGP during grower, finisher, and the entire study ( P < 0.05). On day 42, birds on PRO, 0.2 and 0.3% PGP treatments had lower counts of Escherichia coli and higher lactobacillus spp . in ileum and cecal contents compared to the CON and 0.1% PGP ( P < 0.05). Villus height and villus height to crypt depth ratio of the duodenum were increased ( P < 0.05) in response to dietary AGP, PRO, and 0.3% PGP. The diets containing PRO and different levels of PGP increased superoxide dismutase and glutathione peroxidase activities and decreased malondialdehyde level in serum, liver, and thigh muscle ( P < 0.05). Total polyunsaturated fatty acid and n-3 fatty acid of birds fed PRO and PGP diets were higher than birds in CON and AGP groups ( P < 0.05). In summary, supplementation of PGP could be a potential alternative to AGP in broiler diets due to its combined positive impacts on performance, serum cholesterol, intestinal health, antioxidant activity, and fatty acid profile in meat. Such effects, however, need to be further verified under compromised health or a disease challenge condition.